The Role of QRIS in Transactions in Makassar City UMKM - Sri Astuty (International Humanity Advance, Business & Sciences, 2023)
This study aims to see how the use of QRIS in improving UMKM in Makassar City. This study uses primary data obtained through the distribution of questionnaires to 30 research respondents using simple random sampling techniques and quantitative research methods. Based on the results of the analysis conducted, it shows that the 2 indicators in transactions with preferences for using QRIS for UMKM in Makassar City are 30.44% convenience indicators, and 21% usefulness. The results of the research analysis also show that all research indicators have a very high level of satisfaction in the use of QRIS for UMKM in Makassar City